Unbalanced Coagulation-Fibrinolysis Potential during L-Asparaginase Therapy in Children with Acute Lymphoblastic Leukaemia - Semeraro, N; Montemurro, P; Giordanol, P; Schettini, F; Santoro, N; De Mattia, D; Giordano, D; Conese, M; Colucci, M (Thrombosis and Haemostasis, 1990)
Treatment of acute lymphoblastic leukaemia (ALL) with L-asparaginase (L-asp) may be associated with thrombotic complications, but the pathogenetic mechanisms of thrombus formation and persistence remain unclear. We studied the procoagulant activity (PCA) of peripheral blood mononuclear cells and some components of the plasma fibrinolytic system in L0 children with ALL undergoing remission induction therapy which includes L-asp. Mononuclear cells obtained 14 days after starting L-asp treatment generated significantly higher amounts of PCA (identified as tissue factor) than cells isolated before the first dose of L-asp and 7 days after the cessation of L-asp administration (p <0.01). Augmented PCA coincided with an increase in the plasma D-dimer. The plasma levels of type 1- plasminogen activator inhibitor were found signiticantly elevated during L-asp therapy (p <0.05), whereas plasminogen levels were markedly decreased (p <0.05). These findings suggest that, during the course of L-asp treatment, the coagulation-fibrinolysis balance is shifted towards promotion of fibrin formation and deposition. Although it remains to be conclusively established whether Lasp per se or the concurrent administration of multiple chemotherapeutic agents is responsible for these changes, the latter could contribute to the thrombotic complications associated with remission induction therapy for ALL.